Effects of mass transfer on heat and mass transfer characteristics between water surface and airstream. (July 2018) - Gu, L.D.; Min, J.C.; Tang, Y.C.
Highlights: Heat and mass transfer between water surface and airstream is numerically studied. The heat and mass transfer coefficients both decrease with increasing mass flux. The heat and mass transfer correction factors are unaffected by air velocity. The Chilton-Colburn analogy holds only for low mass flux. The air property variability has a notable effect on heat transfer coefficient. Abstract: A numerical study has been conducted to simulate the convective heat and mass transfer between water surface and air fluid flowing over it. The airflow is laminar and steady, and has a temperature much higher than the water, causing a combined heat and mass transfer accompanied with water evaporation into the airstream. Calculations are performed to investigate the effects of mass flux on heat and mass transfer coefficients and the applicability of the Chilton-Colburn analogy for 200 °C air temperature, 1–10 m/s air velocities, and 10–90 °C water temperatures. Calculations are implemented with and without consideration of the air property variations caused by the air temperature and humidity changes near the water surface and in the airflow direction. The results show that the heat and mass transfer coefficients both decrease with increasing water surface temperature, i.e. increasing mass flux. The Chilton-Colburn analogy holds only for low water temperature case, the deviation of the heat to mass transfer coefficient ratio given by the Chilton-Colburn analogy relative to that by the numerical simulation is less than 5% when the water surface temperature is below 60 °C. The air property variability has a notable and complex effect on heat transfer coefficient but an inconspicuous effect on mass transfer coefficient.